Effect of coconut shell nanopowder reinforcement in the development of palm fiber composites - Raja Dhas, J. Edwin; Savio Lewise, K. Anton; Kumar, K. Naveen; Raja, Vijayanandh; AL-bonsrulah, Hussein A. Z.; Ahmad, Hijaz; Yao, Shao-Wen; Al-Bahrani, Mohammed (Frontiers in Materials, 2022)
Lightweight materials are often produced with high rigidity and specialised qualities for particular applications, saving weight and lowering energy consumption. To accomplish this traditional metals are being replaced by composites in all fields. In the work, cheaper and naturally available coconut shell nano-filler are added to the composite resin system and dispersed uniformly within the polyester resin to improve the overall characteristics of the composites. Sandwiching of palm fibers within the glass fiber combines the strength of both the natural and synthetic fibers. Coconut shell nanoparticles improve the tensile, flexural, impact, hardness and waster absorption characteristics of the material. The existence of palm fibers and their improved adhesion with the pure resin was confirmed by Fourier Transform Infrared Spectroscopy (FTIR) examination which revealed the presence of one additional alcohol/phenol OH stretch, one less alkyl CH stretch and aromatic CH bending functional groups. The inclusion of palm fibers pushed the curves to higher temperatures with considerable degradation temperatures, increasing thermal stability and making it acceptable for thermal applications.